2015
DOI: 10.1371/journal.pone.0136142
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms of Regulation of the Warburg Effect in Lymphoblastoid and Burkitt Lymphoma Cells

Abstract: BackgroundThe Warburg effect is one of the hallmarks of cancer and rapidly proliferating cells. It is known that the hypoxia-inducible factor 1-alpha (HIF1A) and MYC proteins cooperatively regulate expression of the HK2 and PDK1 genes, respectively, in the Burkitt lymphoma (BL) cell line P493-6, carrying an inducible MYC gene repression system. However, the mechanism of aerobic glycolysis in BL cells has not yet been fully understood.Methods and FindingsWestern blot analysis showed that the HIF1A protein was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…amply been reported that genetic and/or pharmacological inhibition of MCT1 and/or 4 in tumour cell lines and mice xenograft models of glioma [38], breast [39], colorectal [40], cervical [41] and lung [42] cancer leads to reduced lactate export, cell proliferation, migration and invasion, and increased responses to radiation and cell death. With respect to lymphomas, MCT4 has been found to be overexpressed in Burkitt's lymphomas and in lymphoblastoid cell lines [43]. Gan et al found that expression of MCT1 was significantly elevated in c-MYC amplified lymphomas, correlating with a poor prognosis and an unfavourable survival.…”
Section: Discussionmentioning
confidence: 99%
“…amply been reported that genetic and/or pharmacological inhibition of MCT1 and/or 4 in tumour cell lines and mice xenograft models of glioma [38], breast [39], colorectal [40], cervical [41] and lung [42] cancer leads to reduced lactate export, cell proliferation, migration and invasion, and increased responses to radiation and cell death. With respect to lymphomas, MCT4 has been found to be overexpressed in Burkitt's lymphomas and in lymphoblastoid cell lines [43]. Gan et al found that expression of MCT1 was significantly elevated in c-MYC amplified lymphomas, correlating with a poor prognosis and an unfavourable survival.…”
Section: Discussionmentioning
confidence: 99%
“…During the rapid proliferation associated with antigenic stimulation, lymphocytes are known to utilize aerobic glycolysis, which results in the generation of large amounts of extracellular lactate, a phenomenon known as the Warburg effect . This phenomenon was originally described in neoplastic cells and occurs in a variety of cancers, including lymphoma . Thus, it is possible that some dogs had an abundance of actively proliferating lymphocytes within the CSF and lactate concentrations in these individuals served as a proliferative marker.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for lymphomas. [106][107][108][109][110][111] Development of multiple myeloma is also supported by essentially the same cell logistics, [112][113][114][115][116][117] and this seems to apply to sarcomas too. [118][119][120][121][122][123] The shared group of functional properties at issue here is in fact a subset of the currently recognized hallmarks of cancer.…”
Section: Related Specific Regulationmentioning
confidence: 97%